Variaions in the protein composition, enzymatic and biological activities in the venom of Bothrops atrox snake (viperidae) in relation to age - Málaga, O. (2014)
Bothrops atrox is the main venomous snake in the Amazonic region of Peru, because it is responsible of the majority of human ophidic accidents. For this reason, variation into chemical composition as well as enzymatic activities on this venom were studied in relation to age, considering 3 groups of captivity snakes: young of 1 and 2 years respectively as well as adult, major of 5 years. The venom obtained from the three groups was pooled, Iyophilized and properly dissolved into saline solution. Protein concentration at 280 nm and by Lowry's method was calculated into each venom sample. Besides, protein bands were determined by PAGE-SIDS. In addition, the following enzymatic activities were determined: caseinolytic, Amidolytic on BAPNA, coagulant, hialuroniclase, L-aminoacidoxidase (LAO) and fosfolipase A 2-Biological effects such as hemorrhage and edema were assayed on white mice. The results showed that high protein concentration (0,938 mg protein/mg venom) and a bigger number of protein bands (8 bands) were found in the venom from young snakes (2 years). Besides, amiclolytic, fosfolipase A2 and LAO as well as hemorrhagic and edematic effects were the most highest in the same samples. In contrast, caseinolytic and coagulant activities were found to increase in proportion to age. Hialuronidase activity decreased with age instead. It was interesting to observe that the venom from adult snakes had only 6,4% folfolipase A2 activity, taking into consideration that the maximum value was obtained with sample of young snakes (2 years).